(untitled) (Law and world, 2019)
Foreign law lies at the heart of the Private International Law. After all, the true conflict of law cannot be resolved unless and until the content of the foreign law is established. The article discusses issues concerning qualification of the foreign law and different viewpoints about it. The foreign law must be provided as a fact, well known both in common law countries, as well as throughout the Continent. During the last century this “fact” theory has lost much of its popularity in civil law countries, while in the UK and in other common law jurisdictions it still dominates over cases, legislation and literature discussions.